Photopolymerization of acrylates by enzymatically synthesized PCL based macrophotoinitiator - N. U. Kaya; A. Onen; Y. Guvenilir (eXPRESS Polymer Letters)
Polycaprolactone based macrophotoinitiator was synthesized via enzymatic ring-opening polymerization by using commercially available Irgacure-2959 as the nucleophilic initiator and Novozyme-435 as the immobilized lipase catalyst. The macrophotoinitiator was further utilized to photopolymerize benzyl acrylate (BzA), tetrahydrofurfurly acrylate (THFA), 2-hydroxyethyl acrylate (HEA) and poly (ethylene glycol) methyl ether acrylate (Mn ~ 480 g/mole) (PEGMEA-480) under Ar atmosphere. The obtained polymers were characterized by 1H Nuclear Magnetic Resonance, Fourier Transform Infrared Spectroscopy, Differential Scanning Calorimetry and Size Exclusion Chromatography. The highest dry polymer conversions were achieved with BzA and THFA. However, due to the gel formation during the photopolymerization reactions of HEA and PEGMEA-480, the dry polymer conversions were comparably lower. The photopolymerization product of BzA demonstrated a single glass transition temperature at –6.5 °C. The enzymatically synthesized macrophotoinitiator was shown to be an efficient catalyst for light-induced polymerization of the abovementioned monomers.